Teacher and Students’ Talk in Speaking Classroom Interaction - Mellany Mellany; Risnawati Risnawati; Fera Zasrianita (Jadila: Journal of Development and Innovation in Language and Literature Education, 2021)
Classroom interactions are typical class situations where verbal contact is dominant, which means that the teacher has a significant impact on the students speaking ability. Classroom interaction and speaking ability have related to created interaction on teaching classroom process. This study purpose at analyzing the realization of classroom interaction especially teacher talk and students talk occurred during teaching speaking class. The data were taken from SMA Negeri 3 Seluma in the form of observation, interview, and documentation. The data then were analyzed by the framework adapted from Flanders Interaction Analysis Categories (FIAC). The findings showed that the classroom interaction most dominant is the teacher while students during speaking class. It also described those teacher roles during classroom interaction as director, manager, and facilitator. The study recommends the teacher support students to actively speak when learning the classroom process. Finally, this study suggests a further study to find various frameworks in analyzing classroom interaction discourse which covers different abilities.